Why more West than East German firms export - Joachim Wagner (Max Planck Institute of Economics, 2007)
Using unique new data and a recently introduced non-linear decomposition technique this paper shows that the huge difference in the propensity to export between West and East German plants is to a large part due to differences in firm size and human capital intensity.
Keywords: F14; 330; Exports; productivity; micro data; Germany; Exportindustrie; Verarbeitendes Gewerbe; Vergleich; Betriebsgröße; Humankapital; Alte Bundesländer; Neue Bundesländer; Deutschland